The holistic rehabilitation from acute severe fever with thrombocytopenia syndrome virus infection to 10 years after recovery: A cross-sectional study - Min Li; Yalan Wang; Peiwen Qiao; Yaxin Guo; Peipei Guo; Tian Ma; Shaobo Dong; Jianbo Zhan; Jun Liu; Guizhen Wu (Biosafety and Health)
Acute viral infections may lead to long-term adverse health effects. Investigating the hematological and biochemical profiles during recovery can provide valuable insights into the prognosis of severe fever with thrombocytopenia syndrome (SFTS) virus infection. Herein, we performed a cross-sectional analysis of 24 hematological parameters and 12 liver and kidney function-related indicators in 143 naturally infected SFTS patients from the acute phase to 10 years post-recovery. Statistical analyses were performed using the Chi-square test (χ2), Fisher’s exact test, or the ANOVA with Bonferroni correction to assess group differences. Most indicators gradually recovered over time during the recovery period. The decrease in platelet (PLT), white blood cell, neutrophil (NEU), and lymphocyte counts in the acute phase showed a gradual recovery trend from 1–8 months to 6–10 years post-recovery. PLT count levels positively correlated significantly with recovery duration (P = 0.0149). NEU % and thrombocytocrit continued to improve with the recovery time. In addition, some indicators, including platelet distribution width, mean platelet volume, and mean corpuscular hemoglobin concentration, continued to show abnormalities in a certain proportion (12.9 %–69.8 %) of individuals post-recovery. For liver and kidney function-related indicators, acute-phase elevations in aspartate aminotransferase and alanine aminotransferase resolved progressively. Direct bilirubin showed a gradual upward trend over time. Additionally, persistent reductions in total protein and albumin were observed in a subset of recovered individuals. These findings highlight the need for long-term monitoring of SFTS survivors and inform clinical management strategies.